STRATEGI KOMUNIKASI PEMASARAN OneFourThree.Co DI INSTAGRAM DALAM MENINGKATKAN BRAND AWARENESS - Ida Fariastuti; Muhammad Abdul Azis (Universitas Prof. Dr. Moestopo (Beragama), 2019)
The purpose this study is to explain the OneFourThree.Co Online Shop marketing communication strategy.The theory used by the author in conducting this research is the Marketing Mix 7P consisting of Product, Price, Place, Promotion, People, Process and Physical Eviden. As a support for this strategy, the author uses the AISAS model, namely Attention, Interest, Search, Action and Share. The paradigm that the author chooses is constructivis by using qualitative approach. This type of research is descriptive research with case study research methods. The results of this study indicate that the marketing communication strategy to increase Brand Awareness is carried out by Brand OneFourThree.Co on Instagram has mostly been done well. Marketing strategy to increase Brand Awareness in order to continue to exist, OneFourThree.Co still has to carry out promotions and improvements so remain in demand by consumers